Changes in Climate Extremes and Their Effect on Maize (Zea mays L.) Suitability Over Southern Africa - Chemura, Abel; Nangombe, Shingirai S.; Gleixner, Stephanie; Chinyoka, Sinclair; Gornott, Christoph (Frontiers in Climate, 2022)
Southern Africa has been identified as one of the hotspot areas of climate extremes increasing, at the same time many communities in the region are dependent on rain-fed agriculture, which is vulnerable to these rainfall and temperature extremes. The aim of this study is to understand changes in extreme indices during the agricultural season under climate change and how that affect the modeling of maize suitability in Southern Africa. We analyze the changes in rainfall and its extreme indices (consecutive dry days, heavy rain events and prolonged rainfall events), and temperature and its extreme indices (hot night temperatures, hot day temperatures and frequency of very hot days) from the past (1986-2014) to the future (2036-2064) and integrate these into a maize suitability model. Temperature extremes are projected to increase in both duration and intensity, particularly in the eastern parts of the region. Also, consecutive dry days are projected to increase over larger areas during the agricultural season, while rainfall will be less in sums, heavier in intensity and less prolonged in duration. Including extreme climate indices in maize suitability modeling improves the efficiency of the maize suitability model and shows more severe changes in maize suitability over Southern Africa than using season-long climatic variables. We conclude that changes in climate extremes will increase and complicate the livelihood-climate nexus in Southern Africa in the future, and therefore, a set of comprehensive adaptation options for the agricultural sector are needed. These include the use of heat, drought and high-intensity rainfall tolerant maize varieties, irrigation and/or soil water conservation techniques, and in some cases switching from maize to other crops.